(untitled) (International journal of artificial intelligence, 2024)
The prevalence of halitosis, its relationship with oral cavity condition and the presence of chronic diseases of the internal organs have been studied with the purpose to develop the algorithm of treating patients with bad breath. Dental checkup has been given to 30 patients aged 26-75 years. The diagnosis of halitosis has been made on the basis of objective presence of bad breath as well as by means of special tests. Patients survey concerning the presence of ENT organs chronic diseases, the digestive system status, the existence of bad habits, constant intake of medicines has been conducted. Halitosis incidence has been determined to make up 93,3% of the total number of the examined patients and to be characterized by the increase of its intensity in the group of patients aged 56-75 years. Among the causes of halitosis the following factors may be noted: bad oral hygiene, the presence of dental hard tissues pathology, the diseases of marginal periodontium and oral mucosa as well as pathological condition of the internal organs. In halitosis oral cavity sanation combined with proper hygienic measures is effective in the majority (80,7%) of cases. If the provided treatment is inefficient complementary examination and treatment by a general practitioner are required.